2018
DOI: 10.1155/2018/3106056
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tight Glycemic Control during Acute Coronary Syndrome on CV Outcome in Type 2 Diabetes

Abstract: Both incidence and mortality of acute coronary syndrome (ACS) among diabetic patients are much higher than those among nondiabetics. Actually, there are many studies that addressed glycemic control and CV risk, whilst the literature on the role of tight glycemic control during ACS is currently poor. Therefore, in this review, we critically discussed the studies that investigated this specific topic. Hyperglycemia is implicated in vascular damage and cardiac myocyte death through different molecular mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
74
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 64 publications
3
74
0
4
Order By: Relevance
“…One of our previous studies has also established the association between impaired cardiac functions and uncontrolled sustained hyperglycaemia in experimental diabetes animal models 4 . Glycaemic control improved the long‐term outcomes and LV mechanical performance of patients with acute coronary syndrome 25 . In this study, our population analysis suggested that HbA1c% was significantly associated with LV systolic dysfunctions in STEMI patients.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…One of our previous studies has also established the association between impaired cardiac functions and uncontrolled sustained hyperglycaemia in experimental diabetes animal models 4 . Glycaemic control improved the long‐term outcomes and LV mechanical performance of patients with acute coronary syndrome 25 . In this study, our population analysis suggested that HbA1c% was significantly associated with LV systolic dysfunctions in STEMI patients.…”
Section: Discussionsupporting
confidence: 51%
“…4 Glycaemic control improved the long-term outcomes and LV mechanical performance of patients with acute coronary syndrome. 25 In this study, our population analysis suggested that HbA1c% was significantly associated with LV systolic dysfunctions in STEMI patients. Moreover, worse LV systolic functions were identified in diabetic MI animals compared with non-diabetic MI animals.…”
mentioning
confidence: 57%
“…As mentioned, glycemic control has not convincingly shown a benefit in the development of cardiovascular complications and mortality. The role of glycemic control during acute myocardial infarction and the subsequent complications in the clinical setting is different, however, and poorly characterized (Sasso et al, 2018). Increased levels of glucose at admission in patients with T2DM are associated with greater mortality risk (Kosiborod et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…About half of the T2D patients have microvascular complications, and about a quarter of patients with T2D have developed macrovascular complications (Litwak et al, 2013). Hyperglycemia induced superoxide overproduction by the mitochondrial electron transport chain via polyol pathway flux, advanced glycation end products, protein kinase C, and the hexosamine pathway is the main reason that T2D is implicated in vascular damage and cardiac myocyte death (Sasso et al, 2018). Several studies suggested that diabetes could be an independent predictor of new cardiovascular events (Sasso et al, 2018;Avogaro et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia induced superoxide overproduction by the mitochondrial electron transport chain via polyol pathway flux, advanced glycation end products, protein kinase C, and the hexosamine pathway is the main reason that T2D is implicated in vascular damage and cardiac myocyte death (Sasso et al, 2018). Several studies suggested that diabetes could be an independent predictor of new cardiovascular events (Sasso et al, 2018;Avogaro et al, 2019). In-hospital appropriate glucose control has a neutral effect on mortality after ACS (Avogaro et al, 2019).…”
Section: Discussionmentioning
confidence: 99%